THE 5 E’S INSTRUCTIONAL MODEL AS A CONSTRUCTIVIST/ CONCEPTUAL CHANGE APPROACH TO ENHANCE STUDENTS’ LEARNING IN SCIENCE - Rahmi Rahmi (FKIP, 2015)
Traditional teaching approach is still applied in most of the schools in the world. There is a critique to traditional teaching approach, because traditional teaching approach does not meet students’ need and fail to prepare students for the demand of society. 5 E’s instructional model is a constructivist/conceptual change approach to teaching. The aims of this paper is to discuss 5 E’s instructional model. Considering to the benefits that have been provided in this paper, it can be concluded that 5 E’s Instructional Model might be a solution to the critiques of traditional approach to teaching and learing. Key Words: The 5 E’s Instructional Model, Constructivist/Conceptual Change Approach, Science learning